2003
DOI: 10.1243/095441003763031789
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft drag reduction—a review

Abstract: The paper summarizes the state of the art in aeronautical drag reduction across the speed range for the`conventional' drag components of viscous drag, drag due to lift and wave drag. It also describes several emerging drag-reduction approaches that are either active or reactive/interactive and the drag reduction potentially available from synergistic combinations of advanced con®guration aerodynamics, viscous drag-reduction approaches, revolutionary structural concepts and propulsion integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 94 publications
1
29
1
Order By: Relevance
“…The detailed review of the methods of laminar flows control is presented by Joslin [16]. The well-grounded papers of Bushnell [17] and Chernyshev et al [18] give valuable information on this problem stated for subsonic, transonic and supersonic aircrafts. The control of the laminar flow enables to reduce the friction drag by about 75-80% comparing to the respective value on a solid impermeable plate.…”
Section: Drag Reduction Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed review of the methods of laminar flows control is presented by Joslin [16]. The well-grounded papers of Bushnell [17] and Chernyshev et al [18] give valuable information on this problem stated for subsonic, transonic and supersonic aircrafts. The control of the laminar flow enables to reduce the friction drag by about 75-80% comparing to the respective value on a solid impermeable plate.…”
Section: Drag Reduction Conceptmentioning
confidence: 99%
“…Except for helicopters and military aircrafts with external loads, which are able to increase the pressure drag noticeably, in most subsonic aircrafts in cruise, the aerodynamic drag normally consists of the friction and due-to-lift drags. For the supersonic aircrafts, the wave drag may be of the same order as the friction drag and vortex resulting from the lifting force [17].…”
Section: Drag Reduction Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest excrescence (insect residue) tends to occur in the area near the stagnation point where whole insect bodies can be collected, but only a limited number cause transition due to the high critical height [15]. The larger the insect excrescence and the farther it is from the stagnation line, the more likely it is to disrupt laminar flow on the aircraft wing [1,15,43]. It has been established that the most critical region of insect impingement occurs from the stagnation point to around 15% chord.…”
Section: Critical Height To Transitionmentioning
confidence: 99%
“…Laminar flow technologies can significantly reduce the drag on aircraft, leading to an increase in airframe aerodynamic efficiency and reduction in fuel consumption, most notably over a long cruise range. A number of studies conducted by aircraft manufacturers, universities, and research institutions -including both large scale wind tunnel and flight tests -have shown the feasibility of these technologies [1][2][3][4][5] that include: Natural Laminar Flow (NLF), Laminar Flow Control (LFC) and Hybrid Laminar Flow Control (HLFC). The use of these concepts is, however, dependent upon the application, as the benefits depend on aircraft size, speed, and wing sweep angle.…”
Section: Introductionmentioning
confidence: 99%